2019
DOI: 10.1016/j.actamat.2018.11.062
|View full text |Cite|
|
Sign up to set email alerts
|

Multiscale investigations of nanoprecipitate nucleation, growth, and coarsening in annealed low-Cr oxide dispersion strengthened FeCrAl powder

Abstract: A major challenge in the design of oxide dispersion strengthened (ODS) FeCrAl alloys is the optimization of the fine-scale particle size distribution that provides both beneficial mechanical properties and irradiation resistance. To address this obstacle, the nucleation, growth, and coarsening of the fine-scale (Y,Al,O) nanoprecipitates within an ODS FeCrAl was studied using atom probe tomography (APT) and small-angle neutron scattering (SANS). Mechanically alloyed Fe-10Cr-6.1Al-0.3Zr+Y2O3 wt.% (CrAZY) powders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…This is in agreement with previous studies that already detect precipitates after annealing at 600°C [31,32,34] and gives the onset of precipitation with an unprecedented precision. Massey et al demonstrated a similar continuous increase of scattering between 200, 400 and 500°C related to the nucleation and growth of Y-Al-O precipitates, different in terms of chemistry but close in terms of manufacturing process [33]. Simultaneously, the apparent volume fraction increases.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…This is in agreement with previous studies that already detect precipitates after annealing at 600°C [31,32,34] and gives the onset of precipitation with an unprecedented precision. Massey et al demonstrated a similar continuous increase of scattering between 200, 400 and 500°C related to the nucleation and growth of Y-Al-O precipitates, different in terms of chemistry but close in terms of manufacturing process [33]. Simultaneously, the apparent volume fraction increases.…”
mentioning
confidence: 88%
“…Precipitates were found in all specimens and were observed to coarsen slightly with increasing temperature. On a Fe-10Cr-11.5Al-Zr-Y ODS alloy, Massey et al observed the nucleation and growth of Y-Al-O precipitates from 200°C to 600°C by in-situ SANS analysis [33]. He et al performed in-situ isothermal holding with temperature ranging up to 1000°C using SANS on a Fe-9Cr ODS steel [34], however the limited flux of the neutron source resulted in sparse data in terms of time resolution.…”
mentioning
confidence: 99%
“…6 the apparent size of the particles as a function of their real size as reported by experimental studies using both SAXS or SANS and APT. The crosses correspond to data from recent literature [41][42][43][44][45][46][47][48][49][50][51] covering a range of alloy systems, including maraging steels, Fe-Cu alloys, ODS-steels, Al-based alloys. We simply plot the values reported in tables or graphs.…”
Section: Comparison With Experimental Reports From the Literaturementioning
confidence: 98%
“…Oxide dispersion strengthened (ODS) alloys are considered as the promising structural material candidate for future advanced reactors, due to their excellent performance [ 1 , 2 , 3 ]. The combined addition of Al and Zr elements to the high Cr (≥13 wt.%) ODS alloys can significantly improve corrosion resistance and strength, based on excellent radiation resistance [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%